GAMBARAN KEMATANGAN KARIR PADA SISWA DI SEKOLAH MENENGAH ATAS - Aini, Aysyah Nur; Nastiti, Dwi (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
Adolescence is a period of complex and dynamic career exploration. This study aims to describe career maturity at Avisena Jabon High School in Sidoarjo. The research employs a descriptive quantitative method with the population consisting of 10th, 11th, and 12th-grade students at Avisena Jabon High School in Sidoarjo. The research sample comprises 248 students selected using the Stratified Random Sampling technique. Data were collected using an adapted career maturity scale and analyzed using the JASP program version 0.19, with reliability (Cronbach's alpha = α=0.989). The results showed that out of the 248 students, 43 (17.34%) were in the low career maturity category, while 205 (82.66%) were in the moderate category. Based on gender, male students have higher career maturity than female students. Science majors (IPA) have better career maturity compared to social studies majors (IPS). Seventeen-year-old students have higher career maturity compared to other ages. The career maturity of students at Avisena Jabon High School in Sidoarjo is mostly in the moderate category. This study implies that guidance and counseling teachers should conduct psychological interventions to improve the career maturity of students in the low category.